2016
DOI: 10.1002/ange.201605504
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐State Chemical Reactivity under Vibrational Coupling to the Vacuum Electromagnetic Field

Abstract: The ground-state deprotection of as imple alkynylsilane is studied under vibrational strong coupling to the zeropoint fluctuations,orv acuum electromagnetic field, of aresonant IR microfluidic cavity.T he reaction rate decreased by af actor of up to 5.5 when the Si À Cv ibrational stretching modes of the reactant were strongly coupled. The relative change in the reaction rate under strong coupling depends on the Rabi splitting energy.P roduct analysis by GC-MS confirmed the kinetic results.T emperature depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
138
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(168 citation statements)
references
References 27 publications
11
138
3
Order By: Relevance
“…Thomas et al 64. have recently demonstrated modification of the kinetics of a chemical reaction when reactant and product vibrational modes are coupled to a cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al 64. have recently demonstrated modification of the kinetics of a chemical reaction when reactant and product vibrational modes are coupled to a cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting hybrid “vibro‐polariton” states exhibit a splitting of the normal mode vibration (the Rabi splitting, ħΩ ) proportional to N , where N is the number of material oscillators present (Figure ) . A few years ago it was discovered that, even in the absence of laser pumping of the optical cavity (the vacuum field regime), VSC influences the kinetics of organic reactions . The kinetic changes are attributed to the vibro‐polariton states, potentially reshaping the Morse potential of molecules and leading to the altered chemical reactivity .…”
Section: Figurementioning
confidence: 99%
“…The kinetic changes are attributed to the vibro‐polariton states, potentially reshaping the Morse potential of molecules and leading to the altered chemical reactivity . To date, studies on VSC chemistry have been reported in deprotection, solvolysis, and addition reactions . Although recent work showed the utility of VSC in organic reactions, the field awaits comprehensive expansion to demonstrate its application for versatile reactions commonly used in organic chemistry.…”
Section: Figurementioning
confidence: 99%
“…Applications of SC in chemistry are only in their infancy, however it has already been shown that formation of these hybrid states can lead to alteration of physical and chemical properties of molecules . Other recent achievements include demonstration of changes in photochemical properties, energy transfer rates, chemical reactivity, Raman scattering enhancement, and Stokes shift control . Furthermore, pioneering theoretical works predict suppression of photochemical reactions, order of magnitude enhancement of electron transfer, or even breaking the Stark–Einstein law …”
Section: Figurementioning
confidence: 99%